Advances in Vertebral Augmentation Systems for Osteoporotic Vertebral Compression Fractures - Yufeng Long; Weihong Yi; Dazhi Yang (Pain Research and Management)
Osteoporotic vertebral compression fracture (OVCF) is a common cause of pain and disability and is steadily increasing due to the growth of the elderly population. To date, percutaneous vertebroplasty (PVP) and percutaneous kyphoplasty (PKP) are almost universally accepted as appropriate vertebral augmentation procedures for OVCFs. There are many advantages of vertebral augmentation, such as short surgical time, performance under local anaesthesia, and rapid pain relief. However, there are certain issues regarding the utilization of these vertebral augmentations, such as loss of vertebral height, cement leakage, and adjacent vertebral refracture. Hence, the treatment for OVCF has changed in recent years. Satisfactory clinical results have been obtained worldwide after application of the OsseoFix System, the SpineJack System, radiofrequency kyphoplasty of the vertebral body, and the Kiva VCF treatment system. The following review discusses the development of the current techniques used for vertebral augmentation.